Optimizing English for Mechanical Engineering through Problem-Based Learning for Students of Mechanical Maintenance and Repair Engineering Study Program Fakfak State Polytechnic: Optimalisasi Pembelajaran Bahasa Inggris 2 (English for Mechanical Engineering) untuk Mahasiswa Program Studi Teknik Perawatan dan Perbaikan Mesin Politeknik Negeri Fakfak - Sukwara Akfan, Sofyan (Politeknik Negeri Fakfak, 2025)
This research aims to enhance students' English technical competence by implementing Problem-Based Learning (PBL) for the English for Mechanical Engineering course at Politeknik Negeri Fakfak. However, the setting of this research is rooted in students' difficulties in understanding technical terms and applying English in engineering work environments. Implementing a participatory action research model with descriptive qualitative approaches, the research was conducted among 50 students of two classes. Data were collected through questionnaires, observations, and interviews. The findings showed that 88% of students perceived the learning material as highly relevant, 84% reported improved mastery over technical vocabulary, and 90% reported greater collaboration and problem-solving skills. Furthermore, the intervention fostered active learning behaviors, peer leadership, and a positive shift towards more favorable attitudes among students towards English as a professional tool. These findings confirm that PBL is a valuable approach to English language learning contextualization in the vocational education context, enhancing the development of both language and soft skills. The research proposes wider implementation of PBL across technical curricula to improve educational outcomes in correspondence with industry requirements.